Impact of pre-treatment INR level on the effect of intravenous low dose vitamin K in patients with excessive anticoagulation - Lubetsky, Aharon; Shasha, Yigal; Olchovsky, David; Loebstein, Ronen; Halkin, Hillel; Ezra, David (Thrombosis and Haemostasis, 2003)
Administration of vitamin K is the common mode of treatment in excessively anticoagulated patients. However, patient’s response to vitamin K varies, depending on the vitamin K dose and the route of administration. Another potential source of variation is the pre-treatment INR which has not been accounted for in most previous studies. In the present study the effect of baseline INR on the response to a single dose of intravenous vitamin K (0.5 mg) was studied in 95 episodes of excessively anticoagulated patients (n = 76).In 67 episodes of moderately excessive baseline INR (6-10) mean INR declined from 8.0 ± 1.2 to 2.6 ± 0.9 at 24 hours, 59/67 (88%) responding within the first 12 hours and not requiring a second dose. In contrast, in 28 episodes with highly excessive baseline INR (> 10) response was slower; mean INR declining from 13.6 ± 2.7 to 4.0 ± 2.1 at 24 hours. In 14/28 of these episodes, patients failed to respond to vitamin K in the first 12 hours and required a second vitamin K dose.We conclude that INR at presentation affects the response to vitamin K and that this INR value should be considered in determining appropriate vitamin K doses.
Keywords: Excessive anticoagulation; vitamin K; baseline INR